Multimetode Sebagai Pendorong Motivasi Dan Hasil Belajar Matematika Kompetensi Dasar Persamaan Linier Dua Variabel - Sari Mulyani (LPMP Provinsi DKI Jakarta, 2021)
Concept in mathematics is very important, especially in the discussion of two-variable linear equations. This study aims to determine the effectiveness of the method given to the motivation and increase in student achievement which is marked by increased learning outcomes. This study used survey analysis which was taken from the results of students' tests in two cycles and the results of the survey. The learning that observes was the basic competency of two variable linear equations for class X-Excact-1 in SMAN 66 Jakarta, at 2019/2020. Observations of the results of the study show that learning using multi methods provides an increase of 20.25% compared to conventional learning. The conclusion from this research is that the use of multiple methods can increase student motivation and achievement